Sociodemographic factors as determinants of fruit and vegetable consumption in Malaysia - Lung, Wei Foon; Yong, Kang Cheah; Nor Azam Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The present study examines the factors afecting fruit and vegetable (FV) consumption in Malaysia. A nationally representative data that consists of a large sample size is used. Hence, the fndings can provide inferential information. The present study uses secondary data from the Malaysian Household Expenditure Survey 2009/2010. The survey was carried out using a two-stage stratifed sampling. The frst stage was based on Enumeration Blocks, while the second stage was based on Living Quarters. A lognormal hurdle model is used to estimate the consumption decision and amount decision of FV across ethnic groups. The results suggest that household size, income, gender, marital status, age and education play signifcant roles in FV consumption. The probability of consuming FV and amount spent increase with household size (p<0.05). Higher income earners are more likely to consume FV than lower income earners (p<0.05). Being male (p<0.05) and unmarried (p<0.05) seem to reduce the consumption likelihood and amount spent. Compared to younger household heads, older household heads have a higher tendency to consume FV (p<0.05). In terms of policy implication, an intervention measure directed toward increasing FV consumption should focus particularly on those who are associated with low FV consumption. In conclusion, household heads’ sociodemographic and household characteristics are important in determining consumption decision and amount decision of FV among Malaysian households.